Oil mill coadjuvants: Aggregation due to moisture and action on olive-pomace oils. (November 2018) - Moya, Manuel; Alcalá, Sonia; Ocaña, María Teresa; Vidal, Alfonso; Espínola, Francisco
Abstract: Pomace is an oil mill byproduct and the raw material for extracting olive pomace oil. The pomace is stored several months in ponds until it is processed. Tests have been carried out in stored olive pastes, malaxated with and without different coadjuvants. These pastes have been equated to the oil mill pomace. Coadjuvants increase the water pH in 0.8 units. 89.5% of the initial oil is recovered from pastes without coadjuvant; 91.1% from pastes with calcium carbonate and 80.5% from pastes with talc. The free acidity is 1.9%, 2.6% and 2.1% respectively. The maximum amount of refined pomace oil is obtained when calcium carbonate is used and the minimum when talc is used. Moisten the adjuvants affects talc and calcium carbonate differently, although both of them easily releases the original micro-powder. Moisture does not affect the technological action of the coadjuvants or modify their physical characteristics. Highlights: Moisture does not alter the technological action of calcium carbonate. In stored pastes, the magnesium favors microbiological activity. More oil is recovered from the pomace ponds with calcium carbonate than with talc The calcium and magnesium soaps in oils represent up to 0.045% and 0.014% by weight.